Immunohistochemical evidence of P2X7R, P2X4R and CaMKK2 in pyramidal neurons of frontal cortex does not align with Alzheimer's disease - Gaff, Jessica; Jackaman, Connie; Papadimitriou, J.; Waters, Shelley; McLean, C.; Price, Patricia (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
Alzheimer's disease (AD) is an incurable neurodegenerative condition resulting in progressive cognitive decline. Pathological features include Aβ plaques, neurofibrillary tangles, neuroinflammation and neuronal death. Purinergic receptors 7 and 4 (P2X7R and P2X4R) and calcium/calmodulin-dependent kinase kinase 2 (CaMKK2) are implicated in neuronal death. We used immunohistochemistry to investigate the distribution of these proteins in neurones from frontal cortex of donors (n = 3/group; aged 79–83 years) who died with and without AD. Neurones were identified morphologically and immunoperoxidase staining was achieved using commercial antibodies. Immunoreactive neurones were counted for each protein by 2–3 raters blinded to the diagnoses. We observed no differences in percentages of P2X7R, P2X4R or CaMKK2 positive neurones (p = 0.2–0.99), but sections from individuals with AD had marginally fewer neurones (p = 0.10). Hence P2X7R, P2X4R or CaMKK2 appear to be expressed in neurones from older donors, but expression does not associate with AD.